On the nature of the current crisis, financial capital vs. productive capital, the real life of the imaginary as an anti-crisis practice. - León, Carlos (Revista Universidad de Guayaquil, 1987)
The text that we collect responds to the central objective of this essay, that is, to contribute to the analysis of the current situation, but starting from the inherent nature of the movement of capitalist private property: its tendency towards concentration and centralization , to monopolization.